Misdiagnosis of appendiceal neoplasms as ovarian tumors: Impact of prior gynecologic surgery on definitive cytoreduction and HIPEC. Issue 2 (February 2022) - Garland- Kledzik, Mary; Maithel, Shelley; Jafari, Mehraneh D.; Dehkordi-Vakil, Farideh; Chaudhry, Haris; Dinicu, Andreea; Chang, Irene; Krasnoff, Chloe; Gambhir, Sahil; Sheehan, Brian; Pigazzi, Alessio
Abstract: Background: Female patients with pelvic/adnexal masses often undergo gynecologic operations due to presumed ovarian origin. The diagnosis of an appendiceal tumor is often only made postoperatively after suboptimal cytoreduction has been performed. We hypothesized that an index gynecological procedure increases the morbidity of definitive cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) in patients with appendiceal mucinous tumors. Methods: A single-center retrospective review was performed to identify female patients undergoing CRS/HIPEC for appendiceal tumors from 2012 to 2020. Results: During the 8-year period, CRS/HIPEC was performed in 36 female patients with appendiceal mucinous tumors. Eighteen patients (50.0%) had received a prior pelvic operation by gynecologists (PPO Group) for presumed ovarian origin before referral for definitive CRS/HIPEC. The median peritoneal cancer index (PCI) was higher in the PPO group (21 vs. 9, p = 0.04). The median number of days from gynecologic procedure to definitive CRS/HIPEC was 169 days. Compared to patients who did not undergo a prior gynecologic operation, those in the PPO group had higher intraoperative blood loss (650 vs 100 mL, p < 0.01) during CRS/HIPEC as well as longer length of stay (12 vs 8 days, p = 0.02) and higher overall morbidity (72.3% vs 33.3%, p = 0.02). After controlling for PCI, prior gynecologic operation increased risk of 30-day morbidity after definitive CRS/HIPEC (OR 11.6, p < 0.01). Conclusion: A multi-disciplinary approach is needed for the primary evaluation of patients with pelvic masses of undetermined origin. A gynecological resection is associated with increased morbidity during definitive cytoreduction and HIPEC for appendiceal mucinous tumors.